Analisis bibliometrik penelitian literasi informasi bidang ilmu sosial periode 2018-2022 - Tupan Tupan (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
Bibliometric analysis of information literacy research in the social field for the 2018-2022 period was carried out based on Scopus data. The analysis aims to find out the main information on social information literacy, sources of social information literacy research results that have an impact, the most cited documents globally, trending topics, keywords that often appear in social information literacy, the most relevant affiliations with information literacy in the field of social, thematic evaluation, and information literacy network maps in the social field. The analysis was carried out using the bibliometric method using the Scopus database for the 2018-2022 period. The results of the analysis show that during the 2018-2022 period there were 1925 documents resulting from information literacy research from 384 different sources. The Journal of Academic Librarianship is the most influential journal with a total of 557 citations. Information literacy, academic libraries, and higher education are trending topics in the period 2019 - 2021. The affiliate that most publishes the highest social information literacy is University Librares. The social field information literacy network map is divided into 4 clusters with the theme that appears most often is information literacy , information retrieval, information seeking, teaching, literacy, internet, and learning